Exploring Differential Effects Across Two Decoding Treatments on Item-Level Transfer in Children With Significant Word Reading Difficulties: A New Approach for Testing Intervention Elements. (3rd July 2016) - Steacy, Laura M.; Elleman, Amy M.; Lovett, Maureen W.; Compton, Donald L.
ABSTRACT: In English, gains in decoding skill do not map directly onto increases in word reading. However, beyond the Self-Teaching Hypothesis, little is known about the transfer of decoding skills to word reading. In this study, we offer a new approach to testing specific decoding elements on transfer to word reading. To illustrate, we modeled word-reading gains among children with reading disability enrolled in Phonological and Strategy Training (PHAST) or Phonics for Reading (PFR). Conditions differed in sublexical training with PHAST stressing multilevel connections and PFR emphasizing simple grapheme-phoneme correspondences. Thirty-seven children with reading disability, 3rd to 6th grade, were randomly assigned 60 lessons of PHAST or PFR. Crossed random-effects models allowed us to identify specific intervention elements that differentially impacted word-reading performance at posttest, with children in PHAST better able to read words with variant vowel pronunciations. Results suggest that sublexical emphasis influences transfer gains to word reading.